An integrated mode to assess service volleyball among power glove, video analysis and testing - Ferrara, F.; Fattore, S.; Pignato, S.; D'Isanto, T. (Journal of Human Sport & Exercise, 2019)
Technological development in recent times has had a rapid spread in various sports to have an improvement in equipment, training methods and performance of athletes through the use of tools. Although in volleyball a good use of video analysis is expected, it is not connected with other technologies. Previous studies have shown that the use of the technological tool, Power Glowe, is able to collect information on force, precision, time impact and direction of the hit when jumping and on the ground. The purpose of the study is to connect and compare the functions of video analysis with those related to the Power Glowe with the actual data on strength, speed, accuracy and tests to assess the effectiveness of the service on a sample divided into 2 groups of female athletes, one from 12 to 16 years and the other from 18 to 26 years old with the aim of comparing the data recruited in a different way. In conclusion, we want to integrate individual methods of data recruitment to optimize the analysis and consequently the evaluation.